PENGARUH STRATEGI PEMBELAJARAN AKTIF TEAM QUIZ TERHADAP MOTIVASI BELAJAR PKn SISWA KELAS VII SMP TRI BHAKTI PEKANBARU - Faizah Husna Husna; Zahirman '; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is aimed to identify the effect of using team quiz active learning strategy on students’ learning motivation of Civic Education in seventh grade students at Junior High School Tri Bhakti Pekanbaru. The population of this research was all seventh grade students of Junior High School Tri Bhakti Pekanbaru which was consisted of 176 students and divided into 5 classes. The sample of this research was VII.3 by 34 students and VII.5 by 36 students, and population in this research consisted of 70 students. The sample of this research was taken by using purposive sampling technique by homogeneity test. The instrument of this research consisted of teachers’ activity, students’ activity, and students’ learning motivation. After the treatment, the percentage of students’ learning motivation in experimental class was 100% of the class population or 36 students and categorized into “very high”. While, the percentage of students’ learning motivation in control class was 97.06% of the class population or 33 students and categorized into “high”, and 1 student or 2.94% of the class population categorized into “low”. Based on the t-test in experimental class and control class, the result of the test showed that t-count > t-table (35.85 > 1.67), it can be concluded that there was significant difference in significance level 5%. The analysis above indicated that the team quiz active learning strategy had effect on students’ learning motivation of Civic Education in seventh grade students at Junior High School Tri Bhakti Pekanbaru. Key Words: team quiz active learning strategy, learning motivation